2018
DOI: 10.1080/01621424.2018.1472702
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of home health care for reducing readmissions: an integrative review

Abstract: This integrative review analyzes research on the relationship of Home Health Care (HHC) to readmissions, specifically, identifying moderating and mediating factors and measurement constraints influencing effectiveness evaluations of HHC in reducing readmissions. HHC patients' readmission rates are higher than patients not receiving home health services but measurement of effectiveness is confounded by both practice variation and comparisons using noncomparable control groups. Effectiveness evaluations of HHC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…Our recent study also found that HHC visits may reduce the need for early readmission after coronary artery bypass grafting [22]. Not all studies have found protective effect of HHC on readmission; however [3,23–25], while we demonstrate that HHC reduces readmission rates in AMI patients, Sud et al . [3] recently explored readmissions in AMI, focusing on patients with ST-elevation myocardial infarction with cardiogenic shock.…”
Section: Discussionsupporting
confidence: 67%
“…Our recent study also found that HHC visits may reduce the need for early readmission after coronary artery bypass grafting [22]. Not all studies have found protective effect of HHC on readmission; however [3,23–25], while we demonstrate that HHC reduces readmission rates in AMI patients, Sud et al . [3] recently explored readmissions in AMI, focusing on patients with ST-elevation myocardial infarction with cardiogenic shock.…”
Section: Discussionsupporting
confidence: 67%
“…Non-skilled services primarily refer to the homemaking assistance provided by home health aids (HA) [17]. HH has been shown to delay nursing home admission in older adults with dementia [18][19][20][21][22][23][24], because it reduces cognitive impairment and functional limitations, the two strongest predictors of nursing home admission [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…reported higher rate of readmission among HHC patients compared to patients without HHC. [ 11 ] They also defined three confounding factors relating HHC to readmissions (HHC eligibility criteria, variation in practice referral and some characteristics of patients that may cause the likelihood to be admitted again). There was no such difference seen in our patient sample.…”
Section: Discussionmentioning
confidence: 99%